The Teaching of Dictionary Use to Multilingual Groups: Traditional (Print) versus Online Dictionaries - OSUCHOWSKA, DOROTA (Journal of Education, Technology and Computer Science, 2018)
Research into dictionary use has demonstrated that students from various national settings differ in the amount of user training they receive. Teachers who work with multilingual groups can try to mitigate the negative effects of this lack of training, but such an endeavor presupposes knowing exactly what skills are needed to handle a dictionary and whether the skills required for traditional print dictionaries differ from those necessary when students avail themselves of dictionaries available online.